Different Techniques for Calculating Apparent and Incremental Inductances using Finite Element Method - Ali, Amer Mejbel (Iraqi Journal for Electrical and Electronic Engineering, 2015)
This work focuses on using two-dimensional finite element method to calculate apparent and incremental inductances for 40W fluorescent lamp ballast with different loading conditions based on its design documents. Seven inductance calculation techniques are adopted by calculating ballast stored magnetic energy and flux linkage using ANSYS software. The calculated results for apparent inductances show a good agreement with the design and average measured values, while calculated incremental inductances have been verified by noting the behavior of core hysteresis loop experimentally. These seven techniques establish a good base for researchers and designers to obtain an accurate inductance profile for any iron-core inductor.